High-frequency modeling of dissolved oxygen and net ecosystem metabolism using STELLA - Miraç Eryiğit; Fatih Evrendilek; Nusret Karakaya (Annals of Limnology and Oceanography - Peertechz Publications, 2023)
This paper proposes a high-frequency process model for estimating Dissolved Oxygen (DO) and net ecosystem metabolism (NEM) in streams. The model was implemented by using STELLA to predict DO concentrations at one-minute intervals downstream of a 150-m headwater reach of the Abant Creek (Bolu, Turkey). NEM was also predicted at each interval by using a two-station method along the reach. DO, water temperature and other environmental variables used in the model were measured during 17 months between August 2015 and December 2016. The model was run for a day representing every month of the year. Model parameters were calibrated and validated according to mean absolute error (MAE) between measured and simulated values of DO and NEM. The results showed that the model appeared to be promising in terms of high-frequency estimations of DO.